EPISTEMOLOGY-DIALECTIC BETWEEN RELIGION AND CULTURE FROM THE PERSPECTIVE OF ANTHROPOLOGISTS - Gusti Pardamean Nasution; Munsarida (Yayasan Dinamika Literasi Jambi, 2025)
This study aims to examine the epistemology-dialectic between religion and culture through the perspective of anthropologists using library research methods. The main focus of this study is to explore how anthropological thinkers understand the reciprocal relationship between religious values and cultural practices that continue to transform along with social dynamics. Through an analysis of classical and contemporary literature from figures such as Clifford Geertz, Emile Durkheim, Bronislaw Malinowski, and Talal Asad, this study finds that religion is not only understood as a symbolic system, but also as a cultural force that shapes patterns of societal behavior. Conversely, culture also influences how religion is practiced , interpreted, and passed down in various social contexts. The research findings show that the relationship between religion and culture is dialectical both negotiate the space of meaning, norms, and collective identity. Thus, this study emphasizes the importance of an anthropological approach in understanding religion as a social and cultural phenomenon, and offers a new epistemological framework for viewing religion and culture as dynamically interacting and intertwined entities.